Race and ethnicity data in the cardiac arrest registry to enhance survival: Insights from medicare self-reported data. (November 2022) - Chan, Paul S.; Merritt, Robert; Chang, Anping; Girotra, Saket; Kotini-Shah, Pavitra; Al-Araji, Rabab; McNally, Bryan
Abstract: Background: For out-of-hospital cardiac arrest (OHCA), assignment of race/ethnicity data can be challenging. Validation of race/ethnicity in registry data with patients' self-reported race/ethnicity would provide insights regarding misclassification. Methods: Using recently linked 2013–2019 Cardiac Arrest Registry to Enhance Survival (CARES) data with Medicare files, we examined the concordance of race/ethnicity in CARES with self-reported race/ethnicity in Medicare. Among patients with unknown race/ethnicity in CARES, race/ethnicity data from Medicare files were reported. Results: Of 26, 875 patients in the linked data, 5757 (21.4%) had unknown race/ethnicity in CARES. Of the remaining 21, 118 patients, 14, 284 (67.6%) were identified in CARES as non-Hispanic White, 4771 (22.6%) as non-Hispanic Black, 1213 (5.7%) as Hispanic, 760 (3.6%) as Asian or Pacific Islander, and 90 (0.4%) as American Indian or Alaskan Native. The concordance rate for race/ethnicity between CARES and Medicare was 93.4% for patients reported as non-Hispanic White in CARES, 89.1% for non-Hispanic Blacks, 74.6% for Hispanics, 69.6% for Asians and Pacific Islanders, and 37.8% for American Indian or Alaskan Natives. For the 5757 patients with unknown race/ethnicity in CARES, 3973 (69.0%) self-reported in Medicare as non-Hispanic White, 617 (10.7%) as non-Hispanic Black, 425 (7.4%) as Hispanic, 491 (8.5%) as Asian or Pacific Islander, and 52 (0.9%) as American Indian or Alaskan Native. Race/ethnicity remained unknown in 199 (3.5%) of patients. Conclusion: Race/ethnicity in CARES was highly concordant with self-reported race/ethnicity in Medicare, especially for non-Hispanic White and Black individuals. For patients with unknown race/ethnicity data in CARES, the vast majority were of White race.